1987
DOI: 10.1128/jb.169.9.3938-3944.1987
|View full text |Cite
|
Sign up to set email alerts
|

Purification and in vitro complementation of mutant histidinol dehydrogenases

Abstract: Genetic and biochemical evidence has indicated that HDH, the product of the hisD gene of S. typhimurium, might display several of these features. In vivo protein complementation experiments (10,18) showed that inactive hisD mutants could be grouped into three classes: hisDa, hisDb, and hisDab. Merodiploid cells containing both hisDa and hisDb mutant genes produced active HDH as judged by cell growth in the absence of histidine. hisDab mutants (the largest class, but mainly frameshift, deletion, and nonsense mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Finally, it has long been known that mutations in the hisD gene fall into two major groups that complement in vivo to produce active enzyme (Greeb et al, 1971), suggesting that the mutations might characterize regions involved in the two HDH half-reactions. However, we have recently used in vitro complementation of purified mutant HDH to show that neither mutant class catalyzed the NAD/NADH exchange reaction reflective of the first oxidation (Lee & Grubmeyer, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has long been known that mutations in the hisD gene fall into two major groups that complement in vivo to produce active enzyme (Greeb et al, 1971), suggesting that the mutations might characterize regions involved in the two HDH half-reactions. However, we have recently used in vitro complementation of purified mutant HDH to show that neither mutant class catalyzed the NAD/NADH exchange reaction reflective of the first oxidation (Lee & Grubmeyer, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of alkaline phosphatase, Fan et al (1966) found nonrandom association of various mutant forms, and specific activities for the complemented products varied. In histidinol dehydrogenase (Lee & Grubmeyer, 1987) heterodimers were strongly favored in mixtures of complementing subunits because the ability of the complemented heterodimer to bind Mn2+ allowed for a thermodynamic pull toward heterodimer formation.…”
Section: Biochemistrymentioning
confidence: 99%
“…1A). Previously described HisD enzymes are homodimers [11,12] containing one Zn 2+ per subunit [11]; and they are 0003-9861/$ -see front matter Ó 2011 Elsevier Inc. All rights reserved. doi:10.1016/j.abb.2011.05.020 therefore examples of metalloenzymes.…”
Section: Introductionmentioning
confidence: 99%